How to break a dragon's heart - Cowell, Cressida (New York : Little, Brown, 2011)
Read the HILARIOUS books that inspired the HOW TO TRAIN YOUR DRAGON films! Hiccup Horrendous Haddock the Third is a smallish Viking with a longish name. Hiccup's father is chief of the Hairy Hooligan tribe which means Hiccup is the Hope and the Heir to the Hairy Hooligan throne - but most of the time Hiccup feels like a very ordinary boy, finding it hard to be a Hero. Whilst searching for his lost friend Camicazi, Hiccup and the Hooligan Tribe have ended up on Uglithug Island.
U
b
b